Expression of genes encoding the luciferase from Photobacterium leiognathi in Escherichia coli Rosetta (DE3) and its application in NADH detection. (19th June 2018) - Xuan, Guanhua; Xiao, Qilin; Wang, Jingxue; Lin, Hong; Pavase, Tushar
Abstract: Cloning of genes encoding the luciferase from Photobacterium leiognathi YL in Escherichia coli Rosetta (DE3) was performed successfully and the expressed forms of lux AB were purified to homogeneity. Experimental measurements revealed that luciferase from Photobacterium leiognathi YL has good thermal stability and a high residual activity at extreme pH values, which are extremely important for its various ecological, industrial and medical applications. Furthermore, we made a first attempt for quantitative detection of NADH by recombinant E. coli Rosetta (DE3) coupled enzyme system. A good linear relationship between luminescence intensity and NADH with low (1–12 nmol/L) and high (10–500 nmol/L) concentration was observed, whose standard curve was y = 772.97 × + 4041.1, R 2 = 0.9884 and y = 1710 × + 4.99 × 10 5, R 2 = 0.9727, respectively. Our results demonstrate a high sensitivity of recombinant E. coli coupled enzyme system to NADH on the basis of high soluble expression of recombinant luciferase and continuous and stable expression of some NAD(P)H‐dependent flavin mononucleotide (FMN) reductases.